Analysis of skeletal stem cells by renal capsule transplantation and ex vivo culture systems - Hsu, Wei; Maruyama, Takamitsu (Frontiers in Physiology, 2023)
Skeletal stem cells residing in the suture mesenchyme are responsible for proper development, homeostasis, and injury repair of the craniofacial skeleton. These naïve cells are programmed to differentiate into osteoblast cell types and mediate bone formation via an intramembranous ossification mechanism. The simplicity of this system also offers great advantages to studying osteoblastogenesis compared to the appendicular and axial skeletons. Recent studies utilizing genetically based cell tracing have led to the identification of skeletal stem cell populations in craniofacial and body skeletons. Although the genetic analysis indicates these cells behave like stem cells in vivo, not all of them have been thoroughly examined by stem cell isolation and stem cell-mediated tissue generation. As regeneration is an integral part of stem cell characteristics, it is necessary to further analyze their ability to generate tissue at the ectopic site. The establishment of an ex vivo culture system to maintain the stemness properties for extended periods without losing the regenerative ability is also pertinent to advance our knowledge base of skeletal stem cells and their clinical applications in regenerative medicine. The purpose of this review is to discuss our recent advancements in analyses of skeletal stem cells using renal capsule transplantation and sphere culture systems.